Principals’ digital transformational leadership, teachers’ commitment, and school effectiveness - Izhak Berkovich; Tahani Hassan (Education Inquiry)
The knowledge about principals’ digital transformational leadership in schools is scarce. This lacuna is problematic because recently many countries switched to remote schooling and online learning models during the COVID-19 pandemic. The new situation changed the principal’s role to one of distant digital leadership, working with teachers and students remotely. The present study aims to investigate principals’ digital transformational leadership and its outcomes. The research is based on data from 380 teachers in Bahrain. The findings and their implications for effective remote schooling are discussed.